Reconstruction of a Highly Twisted Magnetic Flux Rope for an Inter-active-region X-Class Solar Flare - Jiang, Chaowei; Duan, Aiying; Feng, Xueshang; Zou, Peng; Zuo, Pingbing; Wang, Yi (Frontiers in Astronomy and Space Sciences, 2019)
Solar eruptions are manifestation of explosive release of magnetic energy in the Sun's corona. Large solar eruptions originate mostly within active regions, where strong magnetic fields concentrate on the solar surface. Here we studied the magnetic field structure for an exception, which is a peculiar GOES X1.2 flare accompanied with a very fast coronal mass ejection taking place between two active regions, where the magnetic field is relatively weak. The pre-flare magnetic field is reconstructed from the SDO/HMI vector magnetogram, using a nonlinear force-free field extrapolation method. It is found that prior to the flare, there is a highly twisted magnetic flux rope with magnetic field lines winding over 6 turns, which connects the border of a leading sunspot of one active region and the following polarity of the neighboring active region. The flux rope's configuration is highly consistent with the observed sigmoidal coronal loops and filament channels by SDO/AIA. It resides rather low-lying between the active regions such that the torus instability is not able to be triggered. Thus, it is most likely that, due to the strong magnetic twist, the kink instability of the flux rope triggers the eruption.